Review: Phytochemistry and ethnopharmacology of Dracaena trifasciata - WHIKA FEBRIA DEWATISARI; NELSIANI TO’BUNGAN (Smujo International, 2024)
Abstract. Dewatisari WF, To’bungan N. 2024. Review: Phytochemistry and ethnopharmacology of Dracaena trifasciata. Nusantara Bioscience 16: 169-184. Dracaena trifasciata (Prain) Mabb. (syn. Sansevieria trifasciata Prain.) or mother-in-law's tongue, is a species belonging to the genus Dracaena, widely cultivated and used by various communities. This plant is recognized as an ornamental, pollutant-absorbing, and textile material. Its leaves and roots have also been used as traditional remedies across Asia and Africa for cough, flu, respiratory tract inflammation, diarrhea, wound healing, and snakebites. Bioactive compounds found in the roots and leaves include alkaloids, tannins, terpenoids, saponins, steroids, phenols, methyl glucuronate acid, glycosides, cardenolides, polyphenols, carbohydrates, and abamagenin. Therefore, this review aims to provide insights into the phytochemical constituents and pharmacological potential of D. trifasciata. It also explores its use in traditional medicine and prospects for further advancement to promote the broader application. Comprehensive literature studies showed that the attributes of D. trifasciata can be applied as an antibacterial, antioxidant, and anticancer agent, having a promising source of natural compounds for novel drug development. Further investigations are needed to assess the long-term and short-term toxicity associated with the use of this plant material, thereby making it a potential source for the development of modern drugs from natural sources. Considering the extensive application of D. trifasciata as a natural remedy, further investigations are crucial to assess the pharmacological potential and safety.